Antibacterial properties of bioactive glass particle abraded titanium against Streptococcus mutans. (30th April 2018) - Abushahba, Faleh; Söderling, Eva; Aalto-Setälä, Laura; Sangder, Johan; Hupa, Leena; Närhi, Timo O
Abstract: The purpose of this study was to evaluate effects of titanium surfaces air-abraded with particles of Bioglass® 45S5 and three-ZnO and SrO doped compositions on the viability, adhesion and biofilm formation of Streptococcus mutans. A statistically significant decrease in the viability of S. mutans was observed for all titanium discs air-particle abraded with the BAGs (p < 0.001). Also, a significant effect on diminishing biofilm formation on the titanium discs was seen for all BAGs (p < 0.01). No differences were noticed in S. mutans adhesion on titanium surfaces treated with different glasses (p = 0.964). Static SBF immersion experiments showed that after 2 and 48 h the BAG doped with 4 mol% ZnO demonstrated the highest Zn 2+ ion concentration released into SBF (0.2 mg L −1 ). 45S5 BAG demonstrated the highest statistically significant increase in the pH throughout the 120 min of static immersion (p < 0.001). In conclusion, we showed that titanium alloy discs abraded with particles of the experimental compositions and 45S5 BAG had strong antimicrobial activity against S. mutans and they suppressed S. mutans biofilm formation. The antimicrobial activity of 45S5 BAG was attributed to high pH whereas for the Zn-containing BAGs antimicrobial activity was due to steady release of Zn 2+ into the interfacial solution.